Comparative study of patient-based versus case-based teaching in prescription writing skills of second year MBBS students - Jadav, Shilpa P.; Bhansali, Nishant B.; Parmar, Dinesh M. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Prescription writing errors can lead to deficiencies in healthcare. Although prescription writing is a part of the medical students’ curriculum with traditional methods, their prescribing skills are still poor due to inadequate training. To fulfil the need for new educational interventions this study aims to compare patient-based teaching with case-based teaching in improving prescription writing skills of second year MBBS students. Methods: This prospective comparative study was carried out after orientation of participants to prescription writing as per WHO prescribing guidelines (n=71). Group A (n=37) and group B (n=34) were given patient-based teaching and case-based teaching respectively of prescription writing for the same five common clinical conditions. The prescription writing skill was assessed by evaluating the prescriptions written by both the groups and scored by 19-point scoring system. Feedback from the group A students was also taken. Results: Statistical analysis of mean scores of group A (15.90) and group B (13.14) was done by Mann-Whitney U test (p<0.001). Comparison of both the groups for the individual parameters was done by Chi-square test which found significant difference in writing some important parameters like doctor’s registration no., contacts of prescriber, name of the medicine, strength of drug, dosage form, dosing instructions, total quantity of medicine and duration of medication etc. Group A students’ feedback brought out the fact that patient-based teaching is a good tool for teaching and learning. Conclusions: Patient-based teaching for prescription writing improves students’ prescription writing skills in an effective way in comparison with traditional case-based teaching.